(untitled) (Research, Society and Development, 2021)
Around 70% of the pork consumed in Brazil is in the form of processed meat, with bacon being the main one. Although there is indicative information in Brazilian legislation about some identity and quality standards for bacon, there are currently discrepancies between what is in the literature, what is actually practiced in companies and what the inspectors define as ideal. In certain cases, the producer himself defines, together with the inspection, the criteria for these products. Thus, the objective of this study was defined in evaluating the characteristics of bacon produced by natural smoking, its identity and quality standards in order to provide subsidies for production standardization for a local slaughterhouse. Five batches of ham bacon with 3 kg each were used, being collected weekly. These lots were packaged and analyzed between periods of 0, 30, 60 and 90 days. Proximal composition, water activity, pH, color, sodium nitrate and nitrite, sodium chloride and monitoring of lipid oxidation were quantified during storage days. The microbiological assessment was followed during the 90 days of storage, through counting of coagulase-positive Staphylococci, sulphite reducing Clostridia and total yeast and mold counts. Via these analyses, the conclusion is that the product does not present a defined production pattern, each batch being produced with different physical-chemical profiles, however the microbiological control is efficient. Another relevant aspect to be concluded is that the useful life cannot be extended, since the microbiological and oxidative patterns can be compromised.